Corruption and Growth in ASEAN Countries : A Non-Linear Investigation - Jang Haw, Tang; Jerome, Kueh; Shirly Wong, Siew Ling (Human Resource Management Academic Research Society (HRMARS), 2020)
This paper examined the nexus between corruption and economic growth of the Association of Southeast Asian Nations (ASEAN) countries covering the period from 1996 to 2018. Most of the ASEAN countries experiencing high level of corruption associated with robust economic growth performance. This phenomenon is opposite against the prevalent proposition of negative linkage between corruption and economic growth. Therefore, a non-linearity analysis has been incorporated to cover the changes in the effect of corruption on economic growth. This finding revealed there is a significant U-shaped relationship between control of corruption and economic growth of ASEAN countries. In other words, corruption may indirectly facilitate the growth until certain threshold level, ultimately, corruption is substantially reducing growth as corruption level under control. Empirical results indicate that the threshold level of corruption is approximately 1.84 on a 5-point scale of corruption control. This shows that corruption will be detrimental to growth when the corruption level is beyond the threshold level. The speed of adjustment implies that ASEAN countries was vulnerable to the variations as it takes longer time to adjust to long-run equilibrium, particularly on economic growth, trade openness, and inflation. The granger causality test denotes the causality between control of corruption and other variables are mutually complementary.